Topotecan for Relapsed Small-cell Lung Cancer: Systematic Review and Meta-Analysis of 1347 Patients - Horita, Nobuyuki; Yamamoto, Masaki; Sato, Takashi; Tsukahara, Toshinori; Nagakura, Hideyuki; Tashiro, Ken; Shibata, Yuji; Watanabe, Hiroki; Nagai, Kenjiro; Inoue, Miyo; Nakashima, Kentaro; Ushio, Ryota; et al. (Scientific Reports, 2015)
Topotecan is the most reliable chemotherapy regimen for relapsed small-cell lung carcinoma (SCLC). The efficacy and adverse effects of topotecan as reported by previous studies varied greatly. The inclusion criterion was a prospective study that was able to provide data for 6-month over-all survival (OS) rate, 1-year OS rate, objective responses, and/or adverse effects of single agent topotecan as a second line chemotherapy for SCLC, written in English language as a full article. Any topotecan regimen were allowed. Binary data were meta-analyzed with the random-model generic inverse variance method. We included 14 articles consisted of 1347 patients. Pooled values were estimated as follows. <Refractory relapse> Six-month OS rate: 37% (95% CI: 28–46%). One-year OS rate: 9% (95% CI: 5–13%). Response rate: 5% (95% CI: 1–8%). <Sensitive relapse> Six-month OS rate: 57% (95% CI: 50–64%). One-year OS rate: 27% (95% CI: 22–32%). Response rate: 17% (95% CI: 11–23%). <Adverse effect> Grade III/IV neutropenia 69% (95% CI: 58–80%). Grade III/IV thrombopenia 41% (95% CI: 34–48%). Grade III/IV anemia 24% (95% CI: 17–30%). Non-hematorogical events were rare. Chemotherapy-related death 2% (95% CI: 1–3%). In conclusion, Topotecan provided a possibly promising outcome for sensitive-relapse SCLC and poor outcome for refractory relapse SCLC. Adverse events were mainly hematological.